2018
DOI: 10.1038/s41598-018-25602-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of in-Line Filters to Completely Remove Particulate Contamination During a Pediatric Multidrug Infusion Protocol

Abstract: The large number of drugs administered simultaneously to neonates and children in hospital results in the formation of particles that are potentially infused. We have investigated the ability of IV in-line filters to eliminate particulate matter from multidrug infusion lines and so prevent contamination. The impact on particle occurrence of the internal volume of the IV line below the in-line filter was then evaluated. The multidrug therapy given to children was reproduced with and without in-line filtration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 35 publications
1
29
1
1
Order By: Relevance
“…The particulate contaminants can be detectable particles that are visible on visual inspection with sizes ≥50 µm or sub-visible particles that are not detectable on visual inspection with sizes varying between 2 and 50 µm 36 . Both visible and sub-visible particulate contaminations in parenteral fluids or solutions are dangerous [36][37][38][39][40] as these fluids are meant to pass through the blood vessels. The present study showed that the drug products are free from both visible and sub-visible particulate contaminations and their use cannot lead to the deleterious effects of particulate contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The particulate contaminants can be detectable particles that are visible on visual inspection with sizes ≥50 µm or sub-visible particles that are not detectable on visual inspection with sizes varying between 2 and 50 µm 36 . Both visible and sub-visible particulate contaminations in parenteral fluids or solutions are dangerous [36][37][38][39][40] as these fluids are meant to pass through the blood vessels. The present study showed that the drug products are free from both visible and sub-visible particulate contaminations and their use cannot lead to the deleterious effects of particulate contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no standard recommendations have been issued by the three main Pharmacopoeias (European, American and Japanese) for dynamic particle counting. This work has been carried out in our laboratory using a new technique for the dynamic counting of non-visible particles (<50 µm) which indicates the potential particulate load to which patients are exposed [ 16 , 17 , 22 , 32 , 33 , 34 ]. With the use of this appliance, different assembly lines used for infusion protocols in intensive care units (adult, paediatric and neonatal) can be reproduced and studied in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of this appliance, different assembly lines used for infusion protocols in intensive care units (adult, paediatric and neonatal) can be reproduced and studied in vitro. The results obtained make it possible to compare the particulate load of two infusion lines and thus highlight the reduced exposure to particles through the use of filters [ 16 , 17 , 22 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation exists in the lower range of particle sizes evaluated in these studies, which may reduce the ability to accurately determine the total number of particles in a given solution. However, estimates of the number of particles infused in critically ill neonates and children suggest that exposure to particles could approach or exceed 1 million particles measuring ≥2 microns each day 9,46,61,68 . Several investigators have advocated more widespread use of filters, especially for the critically ill 15 .…”
Section: Size and Number Of Particles In Pn Admixturesmentioning
confidence: 99%